2012
DOI: 10.1080/01402382.2012.713744
|View full text |Cite
|
Sign up to set email alerts
|

European Parliament Elections and Political Representation: Policy Congruence between Voters and Parties

Abstract: It is often said that European Parliament elections fail as an instrument to express the will of the European people. However, while the elections are not contested at the European level and are often dominated by national issues, this does not necessarily imply that they fail to connect policy views of voters and representatives. We examine policy congruence between voters and candidates, utilizing the candidate and voter surveys of the European Election Study 2009. First, we demonstrate that policy preferenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
93
1
8

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 25 publications
(23 reference statements)
1
93
1
8
Order By: Relevance
“…However, the attitudinal roots of Euroscepticism also depend on the specific dimension of Euroscepticism under consideration. Previous research on the relation between Euroscepticism and economic and cultural issue dimensions has shown that EU attitudes are consistently and strongly related to cultural positions (Kriesi et al 2008;Van der Brug and Van Spanje 2009), and less so to economic attitudes (Costello et al 2012;Garry and Tilley 2014). No study has however distinguished between different dimensions of EU attitudes.…”
Section: H1bmentioning
confidence: 98%
“…However, the attitudinal roots of Euroscepticism also depend on the specific dimension of Euroscepticism under consideration. Previous research on the relation between Euroscepticism and economic and cultural issue dimensions has shown that EU attitudes are consistently and strongly related to cultural positions (Kriesi et al 2008;Van der Brug and Van Spanje 2009), and less so to economic attitudes (Costello et al 2012;Garry and Tilley 2014). No study has however distinguished between different dimensions of EU attitudes.…”
Section: H1bmentioning
confidence: 98%
“…The survey sample is highly representative of the general population of candidates on these two key characteristics. Costello et al 2012;Leimgruber et al 2010;Reher 2015;Teperoglou et al 2014). Other data have of course been used as well as some scholars have instead opted for party or government positions (e.g., Golder and Stramski 2010;Hakhverdian 2010;Huber and Powell 1994;Powell 2009) and others for the positions of elected parliamentarians (e.g., Hanretty et al 2017;Karyotis et al 2014;Vasilopoulou and Gattermann 2013 viii Responses that did not fall under these categories were omitted from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…x It is important to compare voters' and candidates' policy positions separately across the different survey items as a growing body of literature suggests that voter-elite congruence can vary according to the issue at stake (e.g., Costello et al 2012;Freire and Belchior 2013;Walczak and van der Brug 2012). xi Although there is little evidence from other Western democracies regarding voter-elite congruence on policy agenda at a specific time as existing studies tend to compare elites' issue attention at T with public opinion at T-1, there is some indication that the differences observed here are not unique to Wales.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The problem is that Europarties do not openly compete with each other during EP elections. Some researchers stress the lack of a cohesive system of European-level party representation due to the limits to citizens' participation in EP elections imposed by national borders [17]. Voters elect national rather than European-level parties, although the latter run massive European campaigns.…”
Section: European-level (Supranational) Party Systemmentioning
confidence: 99%